Biomechanical analysis of circles on pommel horse - Fujihara, T.; Fuchimoto, T.; Gervais, P. (Sports Biomechanics, 2009)
The aim of this study was to analyse the principal mechanics of circles. Seventeen university male gymnasts performed circles on an instrumented pommel horse model that enabled the pommel reaction forces to be recorded at 1000 Hz with two force plates. The circles were also videotaped using two digital video cameras operating at 60 frames per second. During circles, the vertical component of the reaction forces peaked in the double-hand support phases. Changes in the velocity of the centre of mass corresponded to the change in the tangential components of horizontal reaction forces. The velocity of the centre of mass had its peaks in the single-hand support phases and its local minimums in the double-hand support phases. The velocity of the ankles and that of the centre of mass of the head and trunk were minimal in the single-hand support phases and were maximal in the double-hand support phases. These results suggest that the circles were composed of vertical movements and two kinds of rotations: rotation of the centre of mass and rotation of the body itself about the centre of mass. These two kinds of rotations, which influence the legs' rotational velocity, are phase dependent. To further our understanding of circles, research on circles in different orientations on the pommel horse will be beneficial.